2018
DOI: 10.1002/jcp.26336
|View full text |Cite
|
Sign up to set email alerts
|

Nucleoskeletal stiffness regulates stem cell migration and differentiation through lamin A/C

Abstract: Stem cell-based tissue engineering provides a prospective strategy to bone tissue repair. Bone tissue repair begins at the recruitment and directional movement of stem cells, and ultimately achieved on the directional differentiation of stem cells. The migration and differentiation of stem cells are regulated by nucleoskeletal stiffness. Mechanical properties of lamin A/C contribute to the nucleoskeletal stiffness and consequently to the regulation of cell migration and differentiation. Nuclear lamin A/C deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 83 publications
(129 reference statements)
0
14
0
Order By: Relevance
“…The processes of MSCs’ migration to injured tissue and differentiation into specific lineage are paramount in bone formation and remodeling. These processes are highly determinate by lamin A/C implication for their correct accomplishment [ 43 ].…”
Section: Lamin A/c and Mscsmentioning
confidence: 99%
See 1 more Smart Citation
“…The processes of MSCs’ migration to injured tissue and differentiation into specific lineage are paramount in bone formation and remodeling. These processes are highly determinate by lamin A/C implication for their correct accomplishment [ 43 ].…”
Section: Lamin A/c and Mscsmentioning
confidence: 99%
“…It is known that cells with higher migration ability tend to have enhanced differentiation potential, but the optimum amount of lamin A/C is different for MSCs’ migration and differentiation [ 43 ]. During bone formation, MSCs migrate until they reach the bone.…”
Section: Lamin A/c and Mscsmentioning
confidence: 99%
“…Finally, the nuclear lamins, and lamin A/C in particular, represent an important determinant of the viscoelastic properties of the nucleus and the entire cell [30]. Higher levels of lamin A, which typically occur in differentiated cells, have been found to promote stiffness in a way that impedes migration in a restrictive 3D environment but enhances stress resistance and cell survival for a broad array of cell types [31,32]. Moreover, the maintenance of low levels of lamin A was recently found to be relevant in granulocytes undergoing chemokineinduced chemotaxis and cell squeezing and extravasation across endothelial barriers under physiological conditions [33].…”
Section: Cytoplasmic and Nuclear Intermediate Filamentsmentioning
confidence: 99%
“…Stem cells with higher migration ability are more sensitive to force and can raise the amount of lamin A/C for later osteogenic differentiation. 73 Other evidence indicated that some factors were connected to both stem cell migration and differentiation. While the involvement of cell-generated force in the connection remained unclear.…”
Section: Stem-cell Migration and Lineage Differentiationmentioning
confidence: 99%